SIMULASI AREA TERDAMPAK BANJIR AKIBAT KERUNTUHAN BENDUNGAN XXX MENGGUNAKAN HEC-RAS 2D - Hanggara, Ikrar; Harifa, Ayisya Cindy; Susilo, Helik; Rahman, Aulia (Prokons: Jurnal Teknik Sipil, 2024)
Dam-break flooding is a disaster that can cause significant infrastructure damage and loss of life. This study aims to model and simulate the flood impact area in the event of the failure of XXX Dam using HEC-RAS (Hydrologic Engineering Center-River Analysis System) software. The simulation considers hydraulic parameters such as flood discharge, watershed topography, and dam characteristics. The results provide flood inundation mapping, water depth, and estimated flood wave arrival time in downstream areas. This study is expected to serve as a reference for disaster mitigation planning and emergency response plans related to dam failure risks. The simulation was conducted using a design flood discharge (Q100) of 425.4 m³/s, modeled to enter the reservoir at a water level of +301 meters. The dam failure was simulated under piping conditions, where the dam height was designed at +301 meters with a length of 160 meters. The flow depth reached up to 12 meters, with flow velocities ranging from 0.2 to 2.8 m/s, which is considered rapid for flood flow. Meanwhile, the flood wave traveled 32 km in 75 minutes. Ten checkpoint locations were established to measure flood impacts on different areas, categorized as mild, moderate, and severe.